Occupational Status and Life Satisfaction in the UK: The Miserable Middle? - Yannis Georgellis; Andrew E. Clark; Emmanuel Apergis; Catherine Robinson (Institute of Labor Economics (IZA), 2022)
We use British panel data to explore the link between occupational status and life satisfaction. We find puzzling evidence, for men, of a U-shaped relationship in cross-section data: employees in medium-status occupations report lower life satisfaction scores than that of employees in either low- or high-status occupations. This puzzle disappears in panel data: the satisfaction of any man rises as he moves up the status ladder. The culprit seems to be immobility: the miserable middle is caused by men who (in our data) have always been in medium-status occupations. There is overall little evidence of a link between occupational status and life satisfaction for women.
Keywords: I31; J24; Z13; 330; occupational status; life satisfaction; occupational mobility